(untitled) (Research, Society and Development, 2021)
Objective: To know the perception of health professionals regarding the care provided to children with chronic conditions. Methodology: This is a descriptive exploratory research with a qualitative approach, carried out with five health professionals who are referrals for family members of children with chronic disease. Data collection took place through semi-structured interviews and were interpreted through thematic analysis. Results: Two thematic units emerged: The recognized importance of multiprofessional care, in contrast to the reality experienced; and The family perceived as the main facilitator or hinderer in the care of children with chronic illness. Discussion: The child with chronic illness needs to be assisted by a multidisciplinary team, in a continuous monitoring in the health services, however, this was identified as a gap in this study. It was also noticed the representativeness of the family in care, through a strengthened and well-defined social network, serving this child from the biopsychosocio-spiritual perspective. Final considerations: Access and availability of trained professionals are essential to meet the demands of children with chronic conditions, and expanded, continuous and resolving care is essential, capable of identifying the biological, emotional and social needs of this population, making full care possible.